Scientific heritage of professor I. S. Tishkevich in development of the criminal-legal doctrine and legislation about crimes against ownership - Moroz, Dmitriy G. (Journal of the Belarusian State University. Law, 2019)
In this article the main stages of scientific activity of professor I. S. Tishkevich, who deeply analyzed the Belarusian criminal law about property crimes and its law enforcement practice in his numerous works are considered. Scientific ideas of the scientist, reflected in the current legislation, or his contained in the scientific literature ideas, which could be of interest to further improvement of the Belarusian criminal law, are analyzed. Consideration of the stated range of issues allowed to come to conclusions about certain directions of further development of the Belarusian criminal legislation about property crimes.
Keywords: property crimes; larceny; object and rest of larceny; objective and subjective aspects of larceny; delimitation of larceny from related crimes